Outcomes analysis in patients with extended-spectrum beta-lactamase bacteremia empirically treated with piperacillin/tazobactam versus carbapenems. Issue 2 (3rd April 2019) - John, Reeba; Colley, Peter; Nguyen, Hoa L.; Berhe, Mezgebe
Abstract: Infections caused by extended-spectrum beta-lactamase (ESBL)-producing bacteria are associated with worse outcomes and have limited treatment options. Carbapenems remain the drug of choice for these infections due to evidence of a mortality benefit and the mixed clinical efficacy associated with piperacillin/tazobactam (PTZ). Though definitive treatment for ESBL infections is well defined, evidence for appropriate empiric therapy remains inconclusive, and the role of rapid molecular assays that identify ESBL has not been evaluated. This multicenter retrospective study at nine Baylor Scott & White Health sites included patients who had positive blood cultures with ESBL-producing bacteria identified by rapid molecular assay and were empirically prescribed PTZ or carbapenems. A total of 117 patients were included in the study; 66 received empiric PTZ and 51 received carbapenems. Results showed no difference in hospital mortality (3% vs 7.8%, P = 0.4), hospital length of stay (6.1% vs 5.9%, P = 0.88), intensive care unit length of stay (4.7% vs 3.3%, P = 0.39), or recurrent ESBL bacteremia (7.6% vs 7.8%, P = 0.99) between the PTZ and carbapenem empiric treatment groups, respectively. In the era of rapid molecular assays, these results suggest that empiric PTZ use and avoidance of empiric carbapenem therapy in the first 24 hours of infection can be considered until a microbiological diagnosis is confirmed.